Study of static and dynamic performances of miniature Savonius-type wind energy harvesters - Han, Nuomin (2018)
Non-polluting and renewable wind energy harnessed by means of large-scale wind turbines has been well-studied and applied. However, the development of miniature wind energy harvesters is left behind due to little attention and effort. In this work, a miniature air-driven Savonius-type energy harvester is three-dimensionally designed. The energy harvester is 3D printed and experimentally tested. Experimental results prove the energy harvester to be associated with a cut-in Reynolds number of 5.95×105 and the maximum overall energy conversion efficiency of 5.16% approximately. To better understand the static and dynamic performances of the designed energy harvester, three-dimensional numerical study is conducted to simulate the experiment. Based on both experimental and numerical results, means to enhance energy harvester's static and dynamic performance are proposed and validated. It is shown that with improved designs, the cut-in Reynolds number can be reduced to 4.33×105 and the overall energy conversion efficiency can be increased to approximately 6.59%.